Identifying economic shocks with stock repurchase programs - Foued Hamouda (Cogent Economics & Finance, 2021)
This paper aims to identify economic shocks in four developed countries that authorize different buyback programs. Previous research has revealed that there are few public debates about buyback activities and economic conditions. According to the free cash flow hypothesis, the total payout policy is in line with the real economy of each country. Using linear and non-linear bivariate causality tests, we find that buybacks and industrial production are endogeniously determined. In Japan, prior buyback programs indicated a change in economic growth. However, in the United States, changes in economic growth will increase repurchase activity before the financial crisis. This finding is interesting because it supports the idea that repurchase programs are a significant factor in determining economic shocks. It has extended and confirmed the knowledge and perception that stock repurchases could be used by financial economists to predict economic shocks.
Keywords: 330; business cycle; buyback; financial crisis; industrial production; payout policy